Villa Cardilio (Torres Novas, Santarém): una revisión desde la Numismática - Conejo Delgado, Noé (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2017)
The archaeological excavations carried out in the Roman villa of Villa Cardilio (Torres Novas, Santarém) have uncovered numerous numismatic findings. The study of these coins and other archaeological objects (ceramics, amphorae, glass, etc.) allows us to reflect on the economy and society of this place, which was dedicated to the residence, human consumption and the possible production of agricultural goods; and its relationship with the rest of the Roman Lusitania.